Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active materials and their preparation and application in lithium batteries
By introducing body-phase doping and gradient heat treatment of specific metals into lithium-rich manganese-based materials, the problem of insufficient structural instability and electrochemical performance of the material under fast charging conditions is solved, and high energy density and excellent fast Filling stability.
Patent Information
- Application Number
- CN202410374707.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-03-29
AI Technical Summary
During the first cycle of lithium-rich manganese-based positive electrode material, irreversible capacity loss due to the irreversible redox reaction of lattice oxygen, severe voltage attenuation, and its layered structure transformed into spinel structure, resulting in a decrease in energy density and poor rate performance. , difficult to adapt to fast charging requirements.
By introducing bulk doping of metals such as W, Ta, Re into lithium-rich manganese-based materials, combined with gradient heat treatment and oxygen atmosphere sintering, a stable oxygen lattice frame is formed, which inhibits lattice oxygen release and structural transformation and improves ionic conductance Rate and reduce grain boundary impedance and improve electrochemical performance.
It significantly improves the crystal structure stability and fast charging stability of lithium-rich manganese-based materials, improves the efficiency and circulation performance of the first circle of Coulomb, increases the lattice constant, increases the Li+ diffusion rate, and forms a high working voltage and excellent plurality. performance.
Smart Images

Figure CN118315578B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of positive electrode materials, and in particular to the field of lithium-rich manganese-based positive electrode materials. Background Art
[0002] As the demand for clean energy in human society increases day by day, the storage of clean energy becomes increasingly important. As a highly efficient energy storage device, lithium-ion batteries provide many conveniences for human life. Due to their high operating voltage, long service life, and green environmental protection, they are widely used in energy storage, electronic products, rail transportation and other fields.
[0003] Since the commercialization of lithium-ion batteries, positive electrode materials have always been the key factor limiting their energy density, power density, and safety performance. In 1991, Thackeray et al. first discovered the lithium-rich manganese-based layered positive electrode material xLi2MnO3·1-xLiMO2 (M=Mn, Co, Ni, etc.) from Li2MnO3. It has attracted widespread attention due to its high discharge specific capacity (>250mAh / g), high energy density and relatively low cost. However, the irreversible redox reaction of lattice oxygen in the lithium-rich manganese layered positive electrode material during the first cycle leads to irreversible capacity loss; during the cycle, Mn 3+ Migration into lithium vacancies, the layered structure transforms into a spinel structure, resulting in severe voltage decay and reduced energy density; the low electronic conductivity of Li2MnO3 makes lithium-rich manganese-based cathode materials have poor rate performance. Therefore, it is crucial to improve the structural stability of lithium-rich manganese-based materials, inhibit lattice oxygen release and alleviate voltage decay.
[0004] In order to solve the above problems, researchers have done a series of modification work such as doping and coating on lithium-rich manganese-based positive electrode materials. For example, the Chinese patent document with publication number CN117637994A discloses a method for preparing a lithium-defect lithium-rich manganese-based positive electrode material. Another example is the Chinese patent document with publication number CN117602684A, which discloses a method for modifying a lithium-rich manganese-based positive electrode material with a molybdenum carbide heterojunction coating. The publication number is CN117199300A, a multi-layer composite structure lithium-rich manganese-based positive electrode material and its preparation method. For another example, the Chinese patent document with publication number CN116706049A discloses a lithium-rich manganese-based positive electrode material with a chemical formula of LiaNibCocMndOeNbfNagKhCsiMgjAlk, where a, b, c, d, e, f are all greater than 0, at least one of g, h, i, j, k is greater than 0 and not less than 0, and f+g+h+i+j+k<a.
[0005] In summary, although there has been a lot of research on the existing technology, there is still much room for improvement in inhibiting capacity decay, stabilizing lattice oxygen, increasing the migration rate of lithium ions, and improving its fast charging stability. Summary of the invention
[0006] In view of the fact that existing lithium-rich manganese-based materials still face problems such as low capacity, easy attenuation, and poor fast charging stability, the first purpose of the present invention is to provide a Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active material aims to provide a lithium-rich manganese-based material with excellent crystal structure stability and excellent electrochemical properties, especially fast charging stability.
[0007] The second object of the present invention is to provide the Li a Mn b Ni c Co x M d M 1 e M 2 f Preparation method of O2 lithium-rich manganese-based active materials and their application in lithium-ion batteries.
[0008] The third object of the present invention is to provide a method comprising the Li a Mn b Ni c Co x M d M 1 e M 2 f Lithium-ion batteries with O2-rich lithium-manganese-based active materials and their positive electrodes and positive electrode materials.
[0009] Lithium-rich manganese-based materials are prone to release lattice oxygen, the crystal structure is prone to change, the grain boundary impedance is large, it is difficult to adapt to the requirements of fast charging applications, and it is difficult to still show excellent stability under fast charging conditions. In response to this problem, the present invention has been studied and provides the following improvement scheme:
[0010] Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active material, wherein M is at least one of W, Ta, and Re, M 1 is at least one of Sc and Y, M 2is at least one of Te, Se, and Si;
[0011] And 1 <a≤1.5;0.4≤b≤0.8;0≤c≤0.4;0≤x≤0.4;0.01≤d≤0.05;0.01<e≤0.05;0.01<f≤0.05;b> c>x.
[0012] The present invention provides a new material with a completely new chemical formula, which is obtained by using the special types of M, M 1 、M 2 The bulk doping can unexpectedly achieve synergy and can unexpectedly effectively solve the problems faced by lithium-rich manganese-based materials, such as easy release of lattice oxygen, easy transformation of crystal structure, large grain boundary impedance, and difficulty in adapting to fast charging application requirements. It can effectively improve its electrochemical properties, especially fast charging stability.
[0013] The present invention also provides a Li a Mn b Ni c Co x M d M 1 e M 2 f The preparation method of O2 lithium-rich manganese-based active material comprises the steps of mixing and proportioning the ingredients according to the chemical formula to obtain a mixed raw material containing various metal raw materials, and then sintering the mixed raw material to obtain the mixed raw material.
[0014] In the present invention, the special types of M, M 1 、M 2 Composite bulk doping of lithium-rich manganese-based materials can unexpectedly stabilize the oxygen lattice framework, inhibit lattice oxygen release, stabilize the crystal structure, inhibit structural transformation, improve ionic conductivity and reduce grain boundary impedance, thereby synergistically improving its electrochemical performance, especially fast charging stability.
[0015] In the present invention, the metal raw material is at least one of a simple substance, oxide, hydroxide, carbonate, sulfate, nitrate, and organic acid salt that can provide at least one metal element;
[0016] Preferably, the mixed raw material comprises a precursor and a source M source, M 1 Source, M 2 Source; the precursor includes hydroxide and / or carbonate of MnNi or MnNiCo.
[0017] In a typical embodiment of the present invention, the mixed raw material comprises a lithium source, a manganese source, a nickel source, and optionally a cobalt source, an M source, and M 1 Source, M 2Source, and each metal raw material can further be a hydroxide, carbonate, oxide, water-soluble salt and other components. Further, the mixed raw material includes a lithium-rich manganese-based precursor, a lithium source, a M source, and a M 1 Source, M 2 The lithium-rich manganese-based precursor is a hydroxide, carbonate, etc. containing nickel, manganese, and optionally cobalt, and can be prepared based on a conventional precipitation reaction.
[0018] In the present invention, the mixed raw material is obtained by solid phase mixing, or by liquid phase mixing followed by desolvation, for example, by drying, spraying, etc.
[0019] In the present invention, as an illustrative embodiment, a is 1.1 to 1.3, a can be 0.4 to 0.55, b can be 0.2 to 0.3, x is 0 to 0.15, d is 0.002 to 0.01, e is 0.002 to 0.02, and f is 0.002 to 0.02.
[0020] In the present invention, the atmosphere in the sintering stage is an oxygen-containing atmosphere, preferably oxygen. 1 、M 2 Under the synergistic bulk phase doping, further combined with the oxygen atmosphere, it helps to further synergize and improve the synergistic bulk phase doping effect of the metal, improve its bulk phase and grain boundaries, and then help to further improve its fast charging stability.
[0021] In the present invention, the temperature of the sintering process is 400-950°C.
[0022] In the present invention, the sintering process includes two heat preservation processes, wherein the temperature of the first heat preservation process is 400-700°C (further 500-550°C); the temperature of the second heat preservation process is 700-950°C (further 800-850°C). 1 、M 2 Under the synergistic bulk phase doping, further combined with the gradient heat treatment process, it is helpful to further synergize and further improve the crystal structure and grain boundaries, thereby further improving its fast charging stability.
[0023] In the present invention, the insulation time of the first insulation process is 1 to 8 hours, and further 4 to 6 hours;
[0024] In the present invention, the insulation time of the second insulation process is 8 to 20 hours, and further 12 to 16 hours.
[0025] In the present invention, at the beginning of sintering, the mixed raw materials and the reinforcing agent are mixed in advance, and then the subsequent sintering process is performed. 1、M 2 Under the synergistic phase doping, further cooperating with the strengthener to assist sintering can help further strengthen the synergistic effect of the special elements, help further improve the crystal structure and grain boundaries, and further improve the fast charging stability of the prepared lithium-rich manganese-based material.
[0026] In the present invention, the strengthening agent includes at least one of lithium nitrate, lithium hydroxide and lithium sulfate;
[0027] Preferably, the reinforcing agent is 1 to 30% of the total molar amount of Li, and further 15 to 25%.
[0028] The present invention also includes Li prepared by the preparation method a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active materials.
[0029] The present invention also includes the Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active materials are used as positive electrode active materials for the preparation of lithium-ion battery applications.
[0030] The present invention also provides a positive electrode material, including a conductive agent, a binder and a positive electrode active material, wherein the positive electrode active material includes the Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active materials.
[0031] In the present invention, in the positive electrode active material, the Li a Mn b Ni c Co x M d M 1 e M 2 fThe content of O2-rich lithium manganese-based active material is above 50wt.%, and can further be the Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active materials.
[0032] In the present invention, the conductive agent and the binder can be conventional components in the industry.
[0033] In the present invention, the weight ratio of the conductive agent, the binder and the positive electrode active material is 1-15:1-15:70-100, and can further be 5-15:5-15:75-85.
[0034] The present invention also provides a positive electrode, including a current collector and a positive electrode material on a composite carrier surface, wherein the positive electrode material is the positive electrode material comprising the Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active material positive electrode material.
[0035] The present invention also provides a lithium ion battery, which comprises the Li a Mn b Ni c Co x M d M 1 e M 2 f O2-rich lithium manganese-based active material positive electrode.
[0036] Beneficial Effects
[0037] The present invention provides a new material, wherein the special types of M, M 1 、M 2 The bulk doping can unexpectedly achieve synergy and unexpectedly effectively solve the problems faced by lithium-rich manganese-based materials, such as easy release of lattice oxygen, easy transformation of crystal structure, large grain boundary impedance, and difficulty in adapting to fast charging application requirements. The lattice constant c of the material described in the present invention increases, Li +The diffusion rate is increased, the release of oxygen is effectively suppressed, and a stable surface structure is formed. The obtained lithium-rich manganese-based positive electrode material has excellent electrochemical properties, high first-cycle coulomb efficiency, good cycle performance, excellent rate performance, high operating voltage, and especially excellent fast charging stability.
[0038] The method of the invention has easy raw material preparation, simple operation and easy industrial production; the obtained material has high average working voltage, good cycle stability and good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The XRD patterns of Example 1 and Comparative Example 1 are shown in Figure 1. The active material prepared in Example 1 was analyzed by XRD. The (003) and (104) peaks of the material shifted to the left, the lattice constant c increased, and the unit cell volume increased. The I(003) / I(104) ratio increased, and the degree of mixing decreased. The release of oxygen was effectively suppressed, and a stable surface structure was formed.
[0040] Figure 2 Cyclic performance diagram of the active material prepared in Example 1 and Comparative Example 1 (1C = 250 mAh / g);
[0041] Figure 3 The cycle performance diagram of the active material prepared in Example 1 and Comparative Example 1 at 12C; DETAILED DESCRIPTION
[0042] The present invention is further described below based on specific implementation examples, but the present invention is not limited to the following specific examples. The methods used in the following implementation examples are conventional methods unless otherwise specified; the reagents and materials described can be obtained from commercial channels unless otherwise specified.
[0043] In the present invention, the precursor may be a precursor of hydroxide, carbonate, etc. containing Mn and Ni, and currently containing Co, which is suitable for lithium-rich manganese in the industry.
[0044] Example 1
[0045] 1g Mn 2 / 3 Ni 1 / 3 (OH)2 precursor powder and tungsten trioxide (M source, WO3), scandium nitrate monohydrate (M 1 Source, Sc(NO3)3·H2O), tellurium dioxide (M 2 The mixture (Li:(Mn+Ni):(M+M 1 +M 2 ) is 1.20:0.79:0.01), in this embodiment, M is 0.003, M 10.003, M 2 The temperature is 0.004, and then the temperature is raised to 500°C (marked as T1) at a rate of 2°C / min in an air atmosphere, and kept at this temperature for 5 hours, and then the temperature is raised to 900°C (marked as T2) at a rate of 1°C / min, and kept at this temperature for 15 hours, and then naturally cooled to room temperature. Thus, the W, Sc, and Te co-doped modified lithium-rich manganese-based positive electrode material (active material) is obtained.
[0046] The crystal structure of the lithium-rich material was analyzed using powder X-ray diffractometer (XRD). Figure 1 As shown in the figure, it can be seen that the material conforms to the crystal peak of lithium-rich material, conforms to the α-NaFeO2 structure, and has no impurity peaks, indicating that the material is of high purity; the (003) / (104) peak shifts to the left, the lattice constant c increases, the unit cell volume increases, and the (003) / (104) ratio is greater than the original sample. + / Ni 2+ The reduction in mixing indicates an ordered ionic arrangement.
[0047] Electrochemical performance test:
[0048] The lithium-rich manganese-based positive electrode material (active material) obtained in the above-mentioned embodiment 1, acetylene black and PVDF were mixed uniformly in a mass ratio of 8:1:1 to form a slurry, which was evenly coated on an aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. Lithium metal foil was used as the negative electrode, Celgard 2400 was used as the separator, and 1M LiPF6 EC / DMC (volume ratio 1:1) solution was used as the electrolyte, and assembled into a CR2016 button battery in a glove box filled with argon.
[0049] The above batteries were subjected to charge and discharge cycle tests in a Blue Power CT2001A battery testing system with a voltage range of 2 to 4.7 V and a test temperature of 25°C.
[0050] Comparative Example 1
[0051] Compared with Example 1, the only difference is that the mixed raw material lacks M source and M 1 Source, M 2 The remaining Li:(Mn+Ni) molar ratio is 1.2:0.8. Other operations, parameters and tests are the same as those in Example 1.
[0052] Figure 2 The performance comparison chart of the modified lithium-rich manganese-based positive electrode material and the control example under a current density of 1C is as follows. The initial capacity at 1C is 232mAh / g, and the capacity retention rate after 200 cycles is 86.01%, which is higher than the capacity of 176mAh / g in the first cycle and the retention rate of 78.70% of the control example 1.
[0053] Figure 3The performance comparison diagram of the modified lithium-rich manganese-based positive electrode material and the comparative example at a current density of 12C is shown. Under high rate 12C conditions, the discharge capacity of comparative example 1 is 80mAh / g, and it can only be cycled 17 times, while the discharge capacity of Example 1 at 12C is 156.1mAh / g, and the capacity retention rate is 86.2% after 200 cycles. The average voltage of the battery in Example 1 is about 3.75V, and the voltage retention rate is 86%, while the average voltage of the battery in Comparative Example 1 is about 3.70V, and the voltage retention rate is 65%.
[0054] Example 2
[0055] Compared with Example 1, the only difference is that yttrium trioxide (Y2O3) is used as M 1 The molar amount of the Y element is the same as that of Sc in Example 1. Other operations, parameters and tests are the same as those in Example 1.
[0056] The results are: its initial capacity at 1C is 228mAh / g, and the capacity retention rate after 200 cycles is 85.52%. Under high rate 12C conditions, the initial capacity is 149.5mAh / g, and the capacity retention rate after 200 cycles is 83.7%. The average voltage of the battery in Example 2 is about 3.72V, and the voltage retention rate is 83%.
[0057] Example 3
[0058] Compared with Example 1, the only difference is that rhenium trioxide (ReO3) is used as the M source, yttrium trioxide (Y2O3) is used as the M1 source, selenium oxide (SeO2) is used as the M2 source, and Li: (Mn+Ni): (M+M 1 +M 2 ) is 1.20:0.75:0.05), in this embodiment, M is 0.01, M 1 0.02, M 2 The temperature T1 is 550°C and the time is 4 hours; the temperature T2 is 850°C and the time is 16 hours; other operations, parameters and tests are the same as those in Example 1.
[0059] Its initial capacity at 1C is 225mAh / g, and the capacity retention rate after 200 cycles is 83.06%. Under high rate 12C conditions, the initial capacity is 145.6mAh / g, and the capacity retention rate after 200 cycles is 83.1%.
[0060] The average voltage of the battery in Example 3 is about 3.70 V, and the voltage retention rate is 81%.
[0061] Example 4
[0062] Compared with Example 1, the only difference is that rhenium trioxide (ReO3) is used as the M source, scandium nitrate (Sc(NO3)3·H2O) is used as the M1 source, selenium oxide (SeO2) is used as the M2 source, and Li: (Mn+Ni): (M+M 1 +M 2 ) is 1.20:0.79:0.01), in this embodiment, M is 0.004, M 1 0.003, M 2 The other operations, parameters and tests are the same as those in Example 1.
[0063] Its initial capacity at 1C is 226 mAh / g, and the capacity retention rate after 200 cycles is 84.36%. Under high rate 12C conditions, the initial capacity is 142.1 mAh / g, and the capacity retention rate after 200 cycles is 84.5%.
[0064] The average voltage of the battery in Example 4 is about 3.72V, and the voltage retention rate is 82%.
[0065] Example 5
[0066] Compared with Example 1, the only difference is that a reinforcing agent is added to the mixture, and the reinforcing agent is lithium nitrate, and the Li element in the lithium nitrate accounts for 20wt% of the total Li molar amount. Other operations, parameters such as the total Li molar amount and tests are the same as in Example 1.
[0067] Its initial capacity at 1C is 233 mAh / g, and the capacity retention rate after 200 cycles is 87.24%. Under high rate 12C conditions, the initial capacity is 158.7 mAh / g, and the capacity retention rate after 200 cycles is 87.1%.
[0068] The average voltage of the battery in Example 5 is about 3.74V, and the voltage retention rate is 87%.
[0069] It can be seen from Examples 1 and 5 that the use of the preferred strengthening agent auxiliary treatment of the present invention can further improve the various properties of the prepared material, especially the fast charging performance and voltage stability, to a certain extent.
[0070] Example 6
[0071] Compared with Example 5, the only difference is that the sintering atmosphere is oxygen. Other operations, parameters and tests are the same as those in Example 1.
[0072] Its initial capacity at 1C is 235 mAh / g, and the capacity retention rate after 200 cycles is 88.65%. Under high rate 12C conditions, the initial capacity is 159.6 mAh / g, and the capacity retention rate after 200 cycles is 88.8%.
[0073] The average voltage of the battery in Example 6 is about 3.71 V, and the voltage retention rate is 88%.
[0074] It can be seen from Examples 1, 5 and 6 that the combined control of the oxygen sintering atmosphere using the preferred strengthener of the present invention can further improve the various properties of the prepared material, especially the fast charging performance and voltage stability, based on the gas-solid-liquid three-phase action.
[0075] Example 7
[0076] Compared with Example 1, the only difference is that, in the sintering stage, the heat preservation process at the temperature T1 is missing, and the heat preservation at the temperature T2 is directly carried out, and the heat preservation time is extended to 17 hours. Other operations, parameters and tests are the same as those in Example 1.
[0077] Its initial capacity at 1C is 219 mAh / g, and the capacity retention rate after 200 cycles is 84.02%. Under high rate 12C conditions, the initial capacity is 146.7 mAh / g, and the capacity retention rate after 200 cycles is 83.9%.
[0078] The average voltage of the battery in Example 7 is about 3.68V, and the voltage retention rate is 79%.
[0079] Example 8
[0080] Compared with Example 1, the only difference is that the chemical formula (Mn 0.526 Ni 0.316 Co 0.158 )CO3 precursor. And Li: (Mn+Ni+Co): (M+M 1 +M 2 ) is 1.20:0.79:0.01), in this embodiment, M is 0.003, M 1 0.003, M 2 The other operations, parameters and tests are the same as those in Example 1.
[0081] Its initial capacity at 1C is 230mAh / g, and the capacity retention rate after 200 cycles is 85.42%. Under high rate 12C conditions, the initial capacity is 150.2mAh / g, and the capacity retention rate after 200 cycles is 86.1%.
[0082] The average voltage of the battery in Example 7 is about 3.72V, and the voltage retention rate is 82%.
[0083] Comparative Example 2
[0084] Compared with implementation 1, the only difference is that the mixed raw material lacks M 2 Source, and the missing M 2Source through the remaining M sources, M 1 The remaining Li in the mixture is (Mn+Ni): (M+M 1 ) is 1.20:0.79:0.01), in this embodiment, M is 0.004, M 1 The other operations and parameters are the same as those in Example 1.
[0085] The test results were as follows: the initial capacity at 1C was 203 mAh / g, and the capacity retention rate after 200 cycles was 80%. Under high rate 12C conditions, the initial capacity was 128.5 mAh / g, and the capacity retention rate after 200 cycles was 67.2%.
[0086] Comparative Example 3
[0087] Compared with implementation 1, the only difference is that the mixed raw material lacks M 1 Source, and the missing M 1 Source through the remaining M sources, M 2 The remaining Li in the mixture is (Mn+Ni): (M+M 2 ) is 1.20:0.79:0.01), in this embodiment, M is 0.005, M 2 The other operations and parameters are the same as those in Example 1.
[0088] The test results were as follows: the initial capacity at 1C was 213 mAh / g, and the capacity retention rate after 200 cycles was 81%. Under high rate 12C conditions, the initial capacity was 102.5 mAh / g, and the capacity retention rate after 200 cycles was 55.3%.
[0089] Comparative Example 4
[0090] Compared with implementation 1, the only difference is that the mixed raw material lacks M source, and the missing M source is replaced by the remaining M 1 Source, M 2 The remaining Li in the mixture is (Mn+Ni): (Mn+Ni): 1 +M 2 ) is 1.20:0.79:0.01), in this embodiment, M 1 is 0.006, M 2 The other operations and parameters are the same as those in Example 1.
[0091] The test results were as follows: the initial capacity at 1C was 215 mAh / g, and the capacity retention rate after 200 cycles was 82%. Under high rate 12C conditions, the initial capacity was 110.7 mAh / g, and the capacity retention rate after 200 cycles was 62.3%.
Claims
1. Li a Mn b Ni c Co x M d M 1 e M 2 f O2 lithium-rich manganese-based active material, characterized in that in, M is at least one of W, Ta, and Re. 1 is at least one of Sc and Y, M 2 is at least one of Te, Se, and Si; And 1 <a≤1.5;0.4≤b≤0.8;0≤c≤0.4;0≤x≤0.4;0.01≤d≤0.05;0.01<e≤0.05;0.01<f≤0.05;b> c>x.
2. The Li according to claim 1 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The ingredients are prepared and mixed according to the stoichiometric ratio of the chemical formula to obtain a mixed raw material containing various metal raw materials, and then the mixed raw material is sintered to obtain; The mixed raw material comprises a lithium-rich manganese-based precursor and an M source, M 1 Source, M 2 Source, Li source; the lithium-rich manganese-based precursor contains nickel, manganese, and optionally contains a hydroxide or carbonate of cobalt.
3. Li as claimed in claim 2 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The metal raw material is at least one of a simple substance, oxide, hydroxide, carbonate, sulfate, nitrate and organic acid salt that can provide at least one metal element.
4. Li as claimed in claim 2 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The mixed raw material is obtained by solid phase mixing, or by desolvation after liquid phase mixing.
5. Li as claimed in claim 2 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The atmosphere during the sintering stage is an oxygen-containing atmosphere.
6. Li as claimed in claim 5 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The atmosphere during the sintering stage was oxygen.
7. Li as claimed in claim 2 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The temperature of the sintering process is 400-950°C.
8. Li as claimed in claim 7 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The sintering process includes two heat preservation processes, wherein the temperature of the first heat preservation process is 400-700°C; and the temperature of the second heat preservation process is 700-950°C.
9. Li as claimed in claim 8 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The insulation time of the first insulation process is 1~8h.
10. Li as claimed in claim 8 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: The insulation time of the second insulation process is 8~20h.
11. Li according to any one of claims 7 to 10 a Mn b Ni c Co x M d M 1 e M 2 f The method for preparing O2 lithium-rich manganese-based active materials is characterized in that: At the beginning of sintering, the mixed raw materials and the reinforcing agent are mixed in advance, and then a subsequent sintering process is performed; The strengthening agent includes at least one of lithium nitrate, lithium hydroxide and lithium sulfate; The reinforcing agent is 1-30% of the total Li molar amount.
12. A positive electrode material, comprising a conductive agent, a binder and a positive electrode active material, characterized in that: The positive electrode active material comprises the Li a Mn b Ni c Co x M d M 1 e M 2 f O2 Lithium-rich manganese-based active material or Li prepared by the preparation method according to any one of claims 2 to 11 a Mn b Ni c Co x M d M 1 e M 2 f O2 Lithium-rich manganese-based active materials.
13. The positive electrode material according to claim 12, characterized in that In the positive electrode active material, the Li a Mn b Ni c Co x M d M 1 e M 2 f The content of O2 lithium-rich manganese-based active material is above 50wt.%.
14. The positive electrode material according to claim 12 or 13, characterized in that The weight ratio of the conductive agent, the binder and the positive electrode active material is 1-15:1-15:70-100.
15. A positive electrode, comprising a current collector and a positive electrode material having a composite carrier surface, characterized in that: The positive electrode material is the positive electrode material according to any one of claims 12 to 14.
16. A lithium ion battery, characterized in that: It comprises the positive electrode according to claim 15.
